Case reportCoronaviruses OC43 and 229E lower respiratory tract co-infections: a clinical report of two cases - Eboriadou, Maria; Haidopoulou, Katerina; Xanthou, Panagiota; Papa, Anna (Archives of Medical Science, 2008)
We report two cases of hospitalized children with human coronavirus (HCoV) co-infection. The first patient was a 6-month female infant admitted for acute bronchiolitis with serologically confirmed respiratory syncytial virus (RSV) infection, while the second one was a 7-year old boy with serologically confirmed Mycoplasma pneumoniae infection. HCoV-OC43 and HCoV-229E were detected in nasopharyngeal aspirate samples of the patients respectively using reverse transcriptase-polymerase chain reaction (RT-PCR). Both children recovered uneventfully. HCoV-229E and HCoV-OC43 usually cause upper respiratory infections; however, rarely, they are associated with lower respiratory tract infection. We discuss their possible role as a co-infectious agent in lower respiratory tract infection.